MECHANISM OF COLLECTION AND DISTRIBUTION OF ZISWAF (ZAKAT, INFAQ, SHODAQOH, WAKAF) FUNDS AT LAZNAS YATIM MANDIRI IN SIDOARJO - Hazra Destatiandra; Putri Qonitah Rahim; Suci Permitasari; Achmad Sjamsudin; DEWI RIZA LISVI VAHLEVI (ICO EDUSHA, 2021)
Zakat, Infaq, Shodaqoh, and Wakaf (ZISWAF) are worship that are not only related to divine values ​​but are also related to socially valuable human relationships (Maliyah ijtimah'iyyah). One of the national zakat institutions, namely Yatim Mandiri, has various programs in optimizing the distribution of ZISWAF funds which are carried out in 46 branch offices throughout Indonesia. The mechanism for collecting and distributing ZISWAF funds is one of the important things that needs to be studied in knowing the factors that cause the distribution of ZISWAF funds in establishing mustahik. This research method is descriptive qualitative research which is literature study and phenomenological study. The results showed that the ZISWAF fund-raising mechanism carried out by LAZNAS Yatim Mandiri Sidoarjo was divided into two, namely direct fundraising and online fundraising. The mechanism for distributing ZISWAF funds carried out by LAZNAS Yatim Mandiri Sidoarjo is managed by program staff to be distributed to various programs that have previously been formulated at the Annual Working Meeting of LAZNAS Yatim Mandiri Sidoarjo. Keywords: ZISWAF, Yatim Mandiri, Fundraising, Distribusing References Berita diakses dari www.yatimmandiri.org. Pada tanggal 21 Juli 2021 Brosur Lembaga Amil Zakat Nasional Yayasan Yatim Mandiri. 2021. Surabaya Majalah Lembaga Amil Zakat Nasional Yayasan Yatim Mandiri. 2021. Surabaya Pedoman Praktik Kerja Lapangan. Sidoarjo. Sekolah Tinggi Agama Islam An Najah Indonesia Mandiri.